Technology foresight - Hardiman, T. P. (Statistical and Social Inquiry Society of Ireland, 1996)
Following the investment in education OECD study in the early sixties the significance of technology to economic development became more apparent. The setting up of the National Science Council under the chairmanship of Professor Colm O hEocha was a result as was the well-informed study and report on technological education led by Professor Noel Mulcahy which brought in its train the establishment of the RTC network strategically located around the regions.
Symposium on Science, Technology, and Innovation: the implications of the STIAC report for Ireland's economic development
Read before the Society, 16 November 1995
Keywords: Technology forecasting; Technological education; 314.15